1995
DOI: 10.1074/jbc.270.39.22795
|View full text |Cite
|
Sign up to set email alerts
|

ADP-ribosylation Factor Translocation Correlates with Potentiation of GTPγS-stimulated Phospholipase D Activity in Membrane Fractions of HL-60 Cells

Abstract: Phospholipase D (PLD) activation by guanine nucleotides requires protein cofactors from both the membrane and the cytosol. The small GTP-binding protein ADP-ribosylation factor (ARF) has been established as one important component of PLD activation. By stimulating HL-60 cells with various agonists and then isolating the membrane fraction and assaying PLD activity in the presence and absence of GTP␥S, we observed that fMet-Leu-Phe (fMLP) and phorbol esters induced a potentiation of GTP␥S-stimulated PLD activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 48 publications
8
59
1
Order By: Relevance
“…Although ARF-responsive PLD activity has been found in other subcellular fractions besides Golgi (plasma membrane, nucleus, and cytosol) (1), its role at these sites is unknown. Some studies have shown agonist-induced membrane translocation of ARF (45,46), but the nature of the membrane target is unclear. Rho regulates the formation of actin stress fibers and focal adhesions (23,24) and has also been implicated in the regulation of phosphatidylinositol 3-kinase (25) and phosphatidylinositol 4-phosphate 5Ј-kinase (26), which synthesize PIP 3 and PIP 2 , respectively.…”
Section: Pkc-␣ and -␤Ii Phosphorylate Rpld1 In Vitro-although The Resmentioning
confidence: 99%
“…Although ARF-responsive PLD activity has been found in other subcellular fractions besides Golgi (plasma membrane, nucleus, and cytosol) (1), its role at these sites is unknown. Some studies have shown agonist-induced membrane translocation of ARF (45,46), but the nature of the membrane target is unclear. Rho regulates the formation of actin stress fibers and focal adhesions (23,24) and has also been implicated in the regulation of phosphatidylinositol 3-kinase (25) and phosphatidylinositol 4-phosphate 5Ј-kinase (26), which synthesize PIP 3 and PIP 2 , respectively.…”
Section: Pkc-␣ and -␤Ii Phosphorylate Rpld1 In Vitro-although The Resmentioning
confidence: 99%
“…PLD1 activation is dependent on the small guanosine triphosphateases (GTPases) adenosine diphosphate (ADP)-ribosylation factor (ARF) and RhoA, one or more PKC isoforms, and phosphatidylinositol-bisphosphate (PIP 2 ), whereas PLD2 activity appears not to involve the GTPases but is primarily stimulated by PIP 2 . 10 Activation of PLD in PMN and HL-60 cells is dependent on ARF and RhoA, 11,12 suggesting that PLD1 is the primary isozyme being measured in previous PMN studies. Both ARF1 and ARF6 have been implicated in PLD activation in phagocytic cells.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that ARF translocation correlated with fMLP-induced PLD activation in HL60 granulocytes [15]. More recently, a concomitant PLD activation and rapid enrichment of RhoA in the particulate fraction was documented in LPAstimulated Rat1 fibroblasts [29] and fMLP-stimulated neutrophils [16].…”
Section: Discussionmentioning
confidence: 99%
“…After extensive washing with buffer B containing 0.025 M NaCl, 0.19 M Tris-HCl, 0.0065 N NaOH, and 0.15% Tween-20, the membranes were incubated with horseradish peroxidase-linked anti-mouse antibody (dilution 1/15,000) or anti-rabbit antibody (dilution 1/15,000), washed again, and then soaked in a chemiluminescence reagent (ECL) for 1 min and then exposed to a film. stimulation of intact cells by PMA or fMLP increased the PLD response to GTP␥S as well as the ARF content in isolated membranes [15]. However, the mechanisms orchestrating the translocation of small GTPases in human granulocytes have yet to be defined.…”
Section: Anti-arf Anti-rhoa and Anti-pkc Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation